2018
DOI: 10.3758/s13415-018-00683-y
|View full text |Cite
|
Sign up to set email alerts
|

Violence in video game produces a lower activation of limbic and temporal areas in response to social inclusion images

Abstract: Exposure to violence in video games has been associated with a desensitization toward violent content, a decrease of empathy, and prosocial behavior. Moreover, violent video games seem to be related to a reduction of neural activation in the circuits linked to social emotional processing. The purpose of the present study was to compare the neural response to social inclusion images after violent and nonviolent video game playing. Electroencephalographic data of the 32 participants were recorded during a visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Chaput et al (2011) showed that video games are associated with pleasure and excitement and that they stimulate the HPA axis, resulting in increased blood pressure and heart rate [7]. Violent video games produced a lower activation of limbic and temporal areas in the brain [6]. In several fMRI scans, the arousal can be shown in brains of video game addicts [8] as well as internet addicts [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaput et al (2011) showed that video games are associated with pleasure and excitement and that they stimulate the HPA axis, resulting in increased blood pressure and heart rate [7]. Violent video games produced a lower activation of limbic and temporal areas in the brain [6]. In several fMRI scans, the arousal can be shown in brains of video game addicts [8] as well as internet addicts [5].…”
Section: Discussionmentioning
confidence: 99%
“…He told me that his father used to play first-person shooter video games when his father was young. The negative influence of violent video games has been investigated as a neural correlate of social capabilities [5,6]. It has been shown that particularly violent games increase the risk of social withdrawal, whereby social support is a known protective factor against mental illness [6].…”
Section: Case Descriptionmentioning
confidence: 99%
“…The artefacts detention was set at 200μV for bad channels (noisy electrodes), at 100μV for eye's blinks, and at 140μV for electrodes revealing eye movements (Electrical Geodesic, Inc., Eugene, OR, USA). 42 44 The segments with an eye blink, an eye movement or more than 30 bad channels were excluded. Baseline correction −100 ms before the onset of the stimulus was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Each voxel served as a source location with three orthogonal orientation vectors, resulting in a total of 2447 source triplets whose anatomical labels were estimated through the use of a Talairach daemon. 42 , 43 , 47 53 …”
Section: Methodsmentioning
confidence: 99%
“…In detailed review, in 25 years of experimental, cross-sectional, longitudinal, and meta-analytical research, the influence of video games, especially violent digital video games on player's aggression was detected (Elson & Ferguson, 2014). Playing of different video games, especially video games with violent content can cause other different problems, such as high reduction of emotional engagement in social processing (Lai et al, 2018).…”
Section: Researches In the World And In Serbiamentioning
confidence: 99%